Search for Wbb(-) and WH production in pp(-) collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
We present a search for Wb (b) over bar production in p (p) over bar collisions at root s=1.96 TeV in events containing one electron, an imbalance in transverse momentum, and two b-tagged jets. Using 174 pb(-1) of integrated luminosity accumulated by the D0 experiment at the Fermilab Tevatron collider, and the standard-model description of such events, we set a 95% C.L. upper limit on Wb (b) over bar production of 6.6 pb for b quarks with transverse momenta p(T)(b)> 20 GeV and b (b) over bar separation in pseudorapidity-azimuth space Delta R-bb> 0.75. Restricting the search to optimized b (b) over bar mass intervals provides upper limits on WH production of 9.0-12.2 pb for Higgs-boson masses of 105-135 GeV.